Group Work and Peer Assessment in Optometry Higher Education. - Zeri, Fabrizio; Cervio, Riccardo; Mosci, Marta; Tavazzi, Silvia; Naroo, Shehzad (Scandinavian Journal of Optometry and Visual Science, 2020)
In health-related professions, education has unique challenges. Problem-based learning can be extremely useful and driven by strategies such as group-work (GW) and peer assessment (PA), which are both used as formative and assessment tools. This study aimed to explore experience and perceptions about GW and PA held by educators and students in optometry. In a first survey, 45 Italian educators (43.8 ± 13.0 years old) of optometric clinical modules answered an email questionnaire investigating their attitudes towards GW and PA. In a second survey, 66 3rd-year undergraduates (22.5 ± 2.0 years old) answered a questionnaire investigating the perception and attitudes towards GW and PA at the beginning and at the end of a module of Advanced Optometry structured with a formative/summative GW activity with a final PA. Two-thirds of optometry educators declared they use GW, but not as a summative assessment tool. Only a quarter of the sample answered that they used PA at least once. Educators’ attitudes towards GW were more positive than PA (p < 0.001). About 60% and 80% of the interviewed students stated they have never participated in GW and PA, respectively. Students’ pre-course attitudes towards GW and PA resulted in values close to the middle of the scale with no significant differences and positive correlations between them (p < 0.001). When students’ GW attitudes were compared with educators’ GW attitudes, the latter were more positive. Students’ post-course attitudes towards GW and PA were enhanced. Although GW and PA are considered very good strategies to improve teaching, the results of the present study have demonstrated that the use of these strategies in Italian optometric higher education is limited. However, the study has also demonstrated that Italian optometry educators have positive attitudes towards “social” teaching strategies especially for GW. Furthermore, optometry students showed improved attitudes towards these strategies once exposed to them. Overall, the results of the study open the possibility to integrate “social” teaching strategies to improve the effectiveness of optometry education.